2003
DOI: 10.2337/diabetes.52.2.434
|View full text |Cite
|
Sign up to set email alerts
|

Age-Dependent Changes in Metabolism, Contractile Function, and Ischemic Sensitivity in Hearts From db/db Mice

Abstract: Glucose and palmitate metabolism and contractile function were measured with ex vivo perfused working hearts from control (db/؉) and diabetic (db/db) female mice at 6, 10 -12, and 16 -18 weeks of age. Palmitate oxidation was increased by 2.2-fold in 6-week-old db/db hearts and remained elevated in 10-to 12-and 16-to 18-week-old hearts. Carbohydrate oxidation was normal at 6 weeks but was reduced to 27 and 23% of control at 10 -12 and 16 -18 weeks, respectively. At 6 weeks, db/db hearts exhibited a slight reduc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

32
239
1
3

Year Published

2003
2003
2018
2018

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 250 publications
(275 citation statements)
references
References 49 publications
32
239
1
3
Order By: Relevance
“…In a study of young women with uncomplicated obesity, our group found that myocardial FA upake, utilization, and oxidation all were increased as BMI and whole body insulin resistance increased, paralleling what was found in animal models of obesity [56,58]. It appears that this increased FA oxidation capacity in humans may also be overwhelmed, as it can be in animal models because autopsy and magnetic resonance spectroscopy studies both demonstrate that in subjects with diabetes there is an increase in intramyocellular triglyceride compared with normal controls [59].…”
Section: Obesity and Myocardial Metabolismsupporting
confidence: 63%
See 1 more Smart Citation
“…In a study of young women with uncomplicated obesity, our group found that myocardial FA upake, utilization, and oxidation all were increased as BMI and whole body insulin resistance increased, paralleling what was found in animal models of obesity [56,58]. It appears that this increased FA oxidation capacity in humans may also be overwhelmed, as it can be in animal models because autopsy and magnetic resonance spectroscopy studies both demonstrate that in subjects with diabetes there is an increase in intramyocellular triglyceride compared with normal controls [59].…”
Section: Obesity and Myocardial Metabolismsupporting
confidence: 63%
“…In response to an increase in FA delivery, the myocardium typically increases betaoxidation of FAs (Figure 2). This increase in beta-oxidation of FAs occurs in animal models of obesity, even before the onset of diabetes [56]. However, it appears that if excessive FA delivery to the myocardium persists, even the myocardium's great capacity for FA oxidation may be overwhelmed leading to increased FA storage (Figure 2).…”
Section: Obesity and Myocardial Metabolismmentioning
confidence: 99%
“…The heart tissues from type 2 diabetic db/db mice and their control db/ϩ mice were kindly provided by Dr. Paul Epstein, University of Louisville. The db/db mice are a well characterized insulin-resistant diabetic model with early onset cardiomyopathy (35). All protocols involving animal use were reviewed and approved by the Internal Animal Care and Use Committee at the University of South Dakota.…”
Section: Methodsmentioning
confidence: 99%
“…[2][3][4] In addition, data from studies conducted in animal models suggest that obesity and insulin resistance cause alterations in myocardial fatty acid metabolism and efficiency (cardiac work/myocardial oxygen consumption) that occur early in the cascade of events that lead to impaired LV contractility. 5,6 In animal models, obesity and insulin resistance increase plasma fatty acid availability and myocardial fatty acid uptake (MFAUp), which causes a shift in substrate metabolism toward a preference for fatty acid utilization (MFAU). 5,6 In these models, there is an initial increase in myocardial fatty acid oxidation (MFAO) and myocardial oxygen consumption (MV O 2 ), which can decrease cardiac efficiency.…”
mentioning
confidence: 99%
“…5,6 In animal models, obesity and insulin resistance increase plasma fatty acid availability and myocardial fatty acid uptake (MFAUp), which causes a shift in substrate metabolism toward a preference for fatty acid utilization (MFAU). 5,6 In these models, there is an initial increase in myocardial fatty acid oxidation (MFAO) and myocardial oxygen consumption (MV O 2 ), which can decrease cardiac efficiency. 6 -9 Over time, a mismatch between MFAUp and MFAO develops and leads to an accumulation of fatty acid intermediates and increased ceramide production, which cause cardiomyocyte apoptosis and impairment of cardiac function.…”
mentioning
confidence: 99%